KDF1 Promoted Proliferation and Metastasis of Epithelial Ovarian Cancer via Wnt/Beta-Catenin Pathway: TCGA-Based Data Mining and Experimental Validation - Zhu, Changyu; Liu, Yilong; Tong, Rongsheng; Guan, Jianmei (Frontiers in Genetics, 2022)
Objectives: The present study was to investigate the function and the potential mechanism of KDF1 in ovarian cancer. Methods: We evaluated prognostic value in ovarian cancer based on data from The Cancer Genome Atlas (TCGA) database. Kurskal-Wallis test, Wilconxon signed-rank test, and logistic regression were used to evaluate the relationship between KDF1 expression and clinical-pathologic features. Cox regression and the Kaplan-Meier method were adopted to evaluate prognosis-related factors. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) gene enrichment analysis as well as Gene set enrichment analysis (GSEA) was performed to identify the key biological process related to KDF1. Then expression of KDF1 in ovarian cancer tissues was validated by streptavidin-perosidase (SP) immunohistochemistry. The proliferation and invasion ability of KDF1 was determined by EdU assay and Transwell assay respectively with KDF1 gene silencing and overexpression. The mRNA expression of KDF1 was determined by qPCR. The protein expression of KDF1 was determined by western blot. Results: By differential expression analysis on the ovarian cancer data of TCGA database, it was found that KDF1 is highly expressed in ovarian cancer patients, And the expression of KDF1 in ovarian cancer patients is related to the overall survival and progression free survival of patients. The high expression of KDF1 associated with platinum resistance and may reduce cell adhesion and promote metastasis of ovarian cancer. At the same time, the BioGRID database showed that there may be protein-protein interaction between KDF1 and E-cadherin. The expression of KDF1 was increased in ovarian cancer tissues compered to normal ovarian tissues. Silencing KDF1 inhibited the proliferation and invasion ability of SKOV3 cells. By contrast, ectopic expression of KDF1 promoted the proliferation and invasion ability of A2780 cells. We also found that KDF1 can interact with E-cadherin and regulate the expression of Wnt5A and β-catenin hence activate wnt/β-catenin pathway. Conclusions: Based on the bioinformatic analysis, in vitro experiments and an in vivo study, it is indicated that KDF1 played an important role in ovarian cancer progress and might be a therapeutic target for patients with ovarian cancer.